LEGAL CONSTRUCTION OF RULE OF REASON APPROACH TO PREDATORY PRICING IN DIGITAL BUSINESS - Ghifari, Naufal; Murwaji, Tarsisius; Harrieti, Nun (Awang Long Law Review, 2025)
The advancement of technology in the business sector is marked by digitalization, enabling transactions to be conducted virtually through platforms, which subsequently gave rise to a new business sector—platform providers. Over time, competition in this sector has increasingly led to unfair business practices, particularly through predatory pricing, which is prohibited. However, the current regulatory framework lacks clear and specific provisions as stipulated under Article 20 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. This ambiguity poses challenges in applying the regulation to concrete cases, particularly in addressing predatory pricing in the digital business context. Consequently, a precise and proportional legal construction is required. This research also employs a descriptive-analytical specification method, which involves outlining the applicable laws and regulations in connection with legal theories and the implementation of positive law practices relevant to the issues examined in this study. The research concludes that Predatory pricing practices in digital business, from the perspective of the Rule of Reason principle, tend towards prohibited below-cost pricing. Therefore, law enforcement necessitates the application of a legal construction based on the guidelines of the Business Competition Supervisory Commission Regulation Number 6 of 2011 concerning Guidelines for Article 20 of Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. However, certain indicators need to be added to enhance the legal framework regulating predatory pricing in digital business through reconstruction by adopting standardized reasonableness criteria and integrating the Per Se Illegal approach to support the realization of legal certainty grounded in efficiency for consumer welfare.